Spodoptera exigua Multiple Nucleopolyhedrovirus Increases the Susceptibility to Insecticides: A Promising Efficient Way for Pest Resistance Management - Shuxing Zhou; Jinming Zhang; Ya Lin; Xiaowei Li; Min Liu; Muhammad Hafeez; Jun Huang; Zhijun Zhang; Limin Chen; Xiaoyun Ren; Wanying Dong; Yaobin Lu (Biology, 2023)
Spodoptera exigua is a polyphagous pest of diverse crops and causes considerable economic losses. The overuse of chemical insecticides for controlling this pest results in insecticide resistance, environmental pollution and toxicity to other non-target organisms. Therefore, a sustainable and efficient way for pest management is urgently required. In this study, laboratory bioassays of eleven commonly used insecticides, the specific entomopathogen of S. exigua (Spodoptera exigua multiple nucleopolyhedrovirus, SeMNPV), and SeMNPV-insecticide combinations against the S. exigua laboratory population and two field populations were tested. Our results indicated that the two field populations had developed resistance to almost half of the tested insecticides, while SeMNPV had good virulence in all populations. Interestingly, the combined use of SeMNPV enhanced the toxicity of the tested insecticides against all populations to a different extent and considerably reduced the insecticide resistance of S. exigua field populations or even recovered the susceptibility to above insecticides. Furthermore, the field trial showed that the combined application of SeMNPV contributed to promoting the control efficacy of emamectin benzonate and chlorfenapyr. These results provide a promising efficient way for pest resistance management and an environmentally friendly approach for controlling S. exigua with the combined application of nucleopolyhedroviruses and insecticides.